Enfrentamento da violência conjugal pela valorização do comportamento assertivo: um modelo de intervenção - Alves, José Lourenço (2017)
Marital violence, which has a high incidence in Brazilian society - even after a decade of application of the Maria da Penha Law - has a profound impact on the quality of life of the couple and their offspring. Considering that the confrontation of this kind of violence requires an approach that is focused on the prevention of its incidence, has short duration and is mixed (evolving men and women), the study aimed to develop an intervention and verify its viability. Classified as an intervention research, it established a relationship between violence, conflict and power, and reached an format aimed at valuing assertive behavior in a situation of marital conflict, considering this behavior as a manifestation of power and resulting from choice. Structured to have 08 participants (04 men and 04 women), in addition to a coordinator, and lasting for 04 hours and 30 minutes, the intervention was divided into three stages: the first informs the applicable concepts, notably assertiveness and its advantages over passivity and aggressiveness; the second applies the designated activity, which consists of the presentation of assertive behavior in situations of marital violence based on real facts; the third seeks to analyze the activity performed, making the opportunity of collecting the comments of the participants and proposing to them an ethical commitment of not attacking in a situation of marital conflict. Applied, the intervention proved to be viable: it took place within the designated time, and the participants stated that they had actualized learnings related to the acceptance of the other, the need to maintain calm in a conflict situation, the importance of dialogue and understanding, having they all assumed the proposed commitment. This is a low cost intervention model that can be applied to people of different educational levels and coordinated by people from different training areas.